Five-year real-world drug survival of dupilumab in severe atopic dermatitis and associate predictors - Francesca Barei; Paolo Calzari; Luca Valtellini; Alessandra Chiei Gallo; Gabriele Perego; Simona Tavecchio; Martina Zussino; Angelo V. Marzano; Silvia Ferrucci (Taylor & Francis Group, 2024)
Background Atopic dermatitis (AD) profoundly impacts patients' lives, necessitating long-term systemic treatments.Methods This retrospective study involved 709 severe AD patients receiving dupilumab. Drug survival (DS) was analyzed using Kaplan-Meier curves, evaluating reasons for discontinuation. The log-rank test and Cox regression analysis were applied to assess differences in drug survival across baseline clinical characteristic groups.Results Dupilumab showcased remarkable overall drug survival, reaching 74.1% at 65 months. Survival rates remained robust even when considering discontinuation solely due to primary or secondary inefficacy (86.4% at 65 months). For overall DS, the log-rank test did not reveal a statistically significant difference among the groups. Cox regression analysis showed that patients with nummular eczema-like as a phenotype have an increased risk of discontinuing dupilumab due to the development of psoriasis (p < .001, hazard ratio = 26.15, confidence interval [CI] 6.903-99.016). The multivariate logistic regression analysis confirmed these results (p < .001, OD = 18.956, CI 4.205-85.458), even when considering other clinical and epidemiological characteristics.Conclusion This investigation establishes dupilumab's enduring efficacy and safety in severe AD, emphasizing its potential as a sustained therapeutic option over 5+ years. Baseline characteristics did not seem to influence DS, with the exception of the nummular eczema-like phenotype, which emerged as a significant predictor of psoriasis occurrence.